2008
DOI: 10.4049/jimmunol.180.3.1719
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pax5 Target Genes in Early B Cell Differentiation

Abstract: The transcription factor Pax5 is essential for B cell commitment in the mouse, where it represses lineage-inappropriate gene expression while simultaneously activating the B cell gene expression program. In this study we have performed a global gene expression screen of wild-type and Pax5-deficient pro-B cells in an attempt to identify the crucial Pax5 targets in early B lymphopoiesis. These studies have identified 109 Pax5 targets comprising 61% activated and 39% repressed genes. Interestingly, Pax5 directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
123
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 62 publications
9
123
0
Order By: Relevance
“…To further investigate changes in gene expression, we performed microarray analysis on samples from wild-type and Stat5b-CA progenitor B cells and Stat5b-CA x Ebf1 +/ leukemic B220 + CD19 + lymph node cells. We then compared our results with previously published datasets of EBF1-and PAX5-activated genes (Schebesta et al, 2007;Pongubala et al, 2008;Pridans et al, 2008;Treiber et al, 2010) and found that the majority of EBF1 and PAX5-induced genes (75.6 and 73.5%, respectively) were unaffected by twofold reductions in Ebf1 and Pax5 expression (Fig. 6 A and Table S2).…”
Section: Ar Ticlementioning
confidence: 68%
See 2 more Smart Citations
“…To further investigate changes in gene expression, we performed microarray analysis on samples from wild-type and Stat5b-CA progenitor B cells and Stat5b-CA x Ebf1 +/ leukemic B220 + CD19 + lymph node cells. We then compared our results with previously published datasets of EBF1-and PAX5-activated genes (Schebesta et al, 2007;Pongubala et al, 2008;Pridans et al, 2008;Treiber et al, 2010) and found that the majority of EBF1 and PAX5-induced genes (75.6 and 73.5%, respectively) were unaffected by twofold reductions in Ebf1 and Pax5 expression (Fig. 6 A and Table S2).…”
Section: Ar Ticlementioning
confidence: 68%
“…The most strongly derepressed of all genes in our analysis is Tnfsf11 (44-fold increase in expression), which encodes RANKL, a factor known to promote progenitor B cell proliferation (Kong et al, 1999). Both EBF1 and PAX5 repress expression of Tnfsf11 (Delogu et al, 2006;Pongubala et al, 2008;Pridans et al, 2008;Treiber et al, 2010). This prompted us to ask whether the list of significantly derepressed genes in our leukemias was enriched in genes regulated by both EBF1 and PAX5.…”
Section: Ar Ticlementioning
confidence: 99%
See 1 more Smart Citation
“…Next, we extracted RNA from these transduced murine BM cells for quantitative real-time PCR analysis. The seven mouse Pax5 target genes, including CD19, Blnk, Rag2, Mb1/CD79a, Blk, Atp1b1 and Nedd9 (Kawamata et al, 2008;Pridans et al, 2008), were selected in our studies. We found that, compared with vector transduction only, introduction of PAX5 into murine BM cells remarkably enhanced the expression of these Pax5 target genes (Figure 1d), which supported these genes are positively regulated by PAX5 transcriptional factor as reported (Cobaleda et al, 2007).…”
Section: Pax5-pml Inhibits the Transcriptional Activity Of Pax5 Targementioning
confidence: 99%
“…205 It is upregulated in short-term HSPCs compared to long-term HSCs, 11 and we found it higher expressed in MPB-compared to BM-derived HSPCs (Fig. 1).…”
mentioning
confidence: 75%